2023
DOI: 10.1007/s11581-023-04944-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical biosensor based on antibody-modified Au nanoparticles for rapid and sensitive analysis of influenza A virus

Abstract: To cope with the easy transmissibility of the avian influenza A virus subtype H1N1, a biosensor was developed for rapid and highly sensitive electrochemical immunoassay. Based on the principle of specific binding between antibody and virus molecules, the active molecule-antibody-adapter structure was formed on the surface of an Au NP substrate electrode; it included a highly specific surface area and good electrochemical activity for selective amplification detection of the H1N1 virus. The electrochemical test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Besides, the performances of such biosensors were compared with other H1N1 electrochemical biosensors in Table S3, wherein the LOD of electrochemical biosensors proposed by Manohara Reddy et al, 27 Park et al, 28 and Bhardwaj et al 53 reached nanomolar (3.09 nM), picomolar (10 pM), and nanomolar (3.45 nM), respectively. The LOD of this sensor increased by 8.974 and 0.224 pg/mL compared to Bai et al 54 and Bao et al, 55 which demonstrated that the electrochemical biosensor in this study exhibited a wide linear range and a lower LOD (1.01 fM). It was probably due to the improved conductivity and higher electroactive surface area of the COFs/MWCNT nanocomposites.…”
Section: Specificity and Stability Of Biosensorsmentioning
confidence: 42%
“…Besides, the performances of such biosensors were compared with other H1N1 electrochemical biosensors in Table S3, wherein the LOD of electrochemical biosensors proposed by Manohara Reddy et al, 27 Park et al, 28 and Bhardwaj et al 53 reached nanomolar (3.09 nM), picomolar (10 pM), and nanomolar (3.45 nM), respectively. The LOD of this sensor increased by 8.974 and 0.224 pg/mL compared to Bai et al 54 and Bao et al, 55 which demonstrated that the electrochemical biosensor in this study exhibited a wide linear range and a lower LOD (1.01 fM). It was probably due to the improved conductivity and higher electroactive surface area of the COFs/MWCNT nanocomposites.…”
Section: Specificity and Stability Of Biosensorsmentioning
confidence: 42%
“…Nowadays, AuNPs are used for the ultrasensitive detection of varied targets [29] such as enzymes [30,31], proteins [32], DNA [33,34], cells [35], viruses [36][37][38][39][40][41], and bacteria [42,43]. Moreover, promising therapeutic approaches have just begun using AuNPs as antiviral agents capable of trapping viruses [44][45][46][47], in anticoagulant therapy [48], in photothermal therapy for breast cancer [49], and in the treatment of inflammatory bowel disease [50].…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has limitations for mass testing applications due to long turnaround times and the need for sophisticated equipment and trained personnel. Electrochemical biosensors have previously been used for the detection of influenza viruses (see Supporting Materials (SM) Table S2) and are rapidly emerging as an alternative to conventional clinical screening techniques. These sensing systems are simple, accurate, and possess a low limit of detection.…”
mentioning
confidence: 99%